Analysis of an Integrative Model of School Commitment: Relationship among Situational, School, Social and Personal Variables in Primary School Students - Rigo, Daiana Yamila (2019)
The study aims at analyzing the predictive role of students' perception about the class’s situational, school, social, and personal variables on the affective, behavioral, and cognitive engagement towards school tasks. The research was developed with 219 students of the primary education level from public schools in Argentina. For data collection,  four standardized instruments were used: –Scale of Engagement towards School Tasks in Primary Level Classes;  Inventory of the Perception of Educational Context as motivator; Questionnaire of Involvement with the School Center and Intrinsic versus Extrinsic Motivational Orientation Scale in the Classroom- as well as the absence record keeping throughout the school year. Furthermore, informed consent was also requested. The model evaluated through Path Analysis presents a good fit to the data (chi square=20.24, df=7, p=.005, chi square/df=2.89,CFI=.99, GFI=.99, RMSEA=.093–CI 90%=.047/.14-), and confirms the hypothesis, i.e., that the affective, behavioral and cognitive engagement is favored by the configuration of the class and the support  from peers and teachers, while personal beliefs mediate absence as school variables that exert a negative influence on every dimension of student involvement.